Comparative analysis of game parameters between Italian league and Israeli league football matches. (3rd March 2020) - Elyakim, Eyal; Morgulev, Elia; Lidor, Ronnie; Meckel, Yoav; Arnon, Michal; Ben-Sira, David
ABSTRACT: The purpose of the current study was to determine the differences between top and average football playing. To do so we analysed 1, 240 matches from the top Israeli and Italian leagues; each match included information on 455 game parameters. A two-phase analysis was performed. In Phase 1 of the analysis we found that the ball movement (e.g., higher number of passes into the box, higher number of key passes), as well as the attack efficiency (higher absolute and relative number of shots from the box, higher number of attacks that entered the box), are significantly superior in the Italian football league. In Phase 2, we identified which game parameters are most important for winning in both leagues. Our results revealed that the success of the matches in both leagues is determined by similar parameters, such as key passes, shots on target, actions up the pitch, and pass precision.